ANALYSIS OF POVERTY RATE AND UNEMPLOYMENT RATE OF HUMAN DEVELOPMENT INDEX IN METRO CITY - Muhamad Irpan Nurhab (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2022)
The Human Development Index (IPM) is used to classify whether a country is developed, developing, or underdeveloped and also to measure the effect of economic policies on quality of life. This study aims to determine and analyze the Human Development Index (IPM) by looking at how significant the influence of the Poverty Rate and Unemployment Rate is on the Human Development Index (IPM) in Metro Lampung City in 2017-2021. The method used in this paper is a literature review supported by quantitative descriptive analysis of secondary data. The secondary data used in HDI development data, poverty rate, and the unemployment rate for 2017-2021 Metro City, Lampung Province. These data are sourced from BPS Kota Metro. The data analysis method used is multiple regression analysis using SPSS to determine the effect of the Poverty and Unemployment rates on the Human Development Index. Based on the results of the calculations that have been carried out, it shows that partially the Poverty Level has no effect on the Human Development Index, for example, partially the Unemployment Rate has an effect on the Human Development Index, and simultaneously the Poverty Rate and Unemployment Rate have no effect on the Human Development Index